2017
DOI: 10.5194/acp-17-3619-2017
|View full text |Cite
|
Sign up to set email alerts
|

Optical and geometrical properties of cirrus clouds in Amazonia derived from 1 year of ground-based lidar measurements

Abstract: Abstract. Cirrus clouds cover a large fraction of tropical latitudes and play an important role in Earth's radiation budget. Their optical properties, altitude, vertical and horizontal coverage control their radiative forcing, and hence detailed cirrus measurements at different geographical locations are of utmost importance. Studies reporting cirrus properties over tropical rain forests like the Amazon, however, are scarce. Studies with satellite profilers do not give information on the diurnal cycle, and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 76 publications
6
43
0
6
Order By: Relevance
“…These results are consistent with Platt and Dilley () where they found that the lidar ratio overall decreased with cloud temperature. Gouveia et al () and Seifert et al () also showed little dependence of observed lidar ratio on temperature. Chen et al () showed an increase of lidar ratio with increasing cloud temperature for a similar temperature range (~200 to 230 K) in which the lidar ratio increased from the present RL observations.…”
Section: Relationship Of Lidar Ratio and Temperaturementioning
confidence: 91%
“…These results are consistent with Platt and Dilley () where they found that the lidar ratio overall decreased with cloud temperature. Gouveia et al () and Seifert et al () also showed little dependence of observed lidar ratio on temperature. Chen et al () showed an increase of lidar ratio with increasing cloud temperature for a similar temperature range (~200 to 230 K) in which the lidar ratio increased from the present RL observations.…”
Section: Relationship Of Lidar Ratio and Temperaturementioning
confidence: 91%
“…This leads to a wrong attenuation correction and thus to wrong quasi-particle-backscatter coefficient and quasi-particle depolarization ratio values above the cloud base. Furthermore, multiple scattering at the large cloud hydrometeors leads to an additional underestimation of the light attenuation (see Seifert et al, 2007;Kienast-Sjögren et al, 2016, or Gouveia et al, 2017. For that reason, the current lidar stand-alone approach is trustworthy only at cloud bases and a few tens of metres above, depending on the cloud optical thickness.…”
Section: April 2013mentioning
confidence: 99%
“…In this study, for accurately correcting the MS influence, we perform a full treatment of multiple scattering following the model of Hogan (2008). The model is also introduced and applied by Seifert et al (2007), Kienast-Sjögren et al (2016) and Gouveia et al (2017). In this model, the typically operated FOV of 1.3 mrad and the full divergence angle of 0.5 mrad in WACAL is input.…”
Section: Multiple Scattering Correctionmentioning
confidence: 99%